2014
DOI: 10.1128/jvi.00728-14
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Gag-Specific CD4 T Cell Responses during Acute HIV Infection Is Associated with Improved Viral Control

Abstract: Effector CD4 T cell responses have been shown to be critically involved in the containment and clearance of viral pathogens. However, their involvement in the pathogenesis of HIV infection is less clear, given their additional role as preferred viral targets. We previously demonstrated that the presence of HIV-specific CD4 T cell responses is somewhat associated with HIV control and that specific CD4 T cell functions, such as direct cytolytic activity, can contribute to control of HIV viremia. However, little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 38 publications
0
41
1
1
Order By: Relevance
“…On one hand, they are intimately associated with protection through the provision of T-cell help for antibody production (34) and possibly direct cytolytic activity (9,25,(107)(108)(109). On the other hand, as predicted by Staprans et al (46) and confirmed elsewhere (97,98) in nonhuman primate studies, they can attenuate protection and lead to increased acquisition.…”
Section: Strategies To Elicit Continuous Protection Against Hiv By Vamentioning
confidence: 83%
“…On one hand, they are intimately associated with protection through the provision of T-cell help for antibody production (34) and possibly direct cytolytic activity (9,25,(107)(108)(109). On the other hand, as predicted by Staprans et al (46) and confirmed elsewhere (97,98) in nonhuman primate studies, they can attenuate protection and lead to increased acquisition.…”
Section: Strategies To Elicit Continuous Protection Against Hiv By Vamentioning
confidence: 83%
“…The breadth and specificity of HS CD4 + T cell responses are associated with improved viral control and low viremia during acute and chronic infection, respectively (2,3). In particular, the generation of Gag-specific CD4 + T cells and their maintenance correlate with a better disease outcome and viral control, respectively (2,3).…”
Section: A Ccumulating Evidence Suggests That Hiv-specific (Hs) Cd4mentioning
confidence: 99%
“…To achieve this, we utilized an IFN-␥ secretion ELISPOT assay that we along with other investigators have used extensively to map T cell responses (13)(14)(15)(16). Using this assay, we were able to show increased HIVspecific CD4 ϩ T cell targeting in subjects with neutralizing breadth, but the caveats of this approach are that we were not able to delineate peripheral Tfh cells, and we were not able to investigate the functional characteristics of CD4 ϩ T cells that may be associated with optimal CD4 ϩ help to B cells.…”
Section: Fig 7 the Magnitude Of Gag-specific Cd4mentioning
confidence: 99%
“…Although HIV-specific CD4 ϩ T cell responses have been shown to be an important feature of viral immunity (10)(11)(12)(13)(14)(15)(16)(17)(18)(19), the specificity, function, and phenotypic characteristics of peripheral HIV-specific CD4…”
mentioning
confidence: 99%